1975
DOI: 10.1002/art.1780180303
|View full text |Cite
|
Sign up to set email alerts
|

Depression of cellular‐mediated immunity in systemic lupus erythematosus

Abstract: Cellular‐mediated immunity was examined in 6 consecutive patients with active SLE, 6 patients with low active SLE, 6 patients with DLE, 8 patients with other collagen diseases, and 9 healthy controls. The following parameters were measured: delayed hypersensitivity, in vitro lymphocyte blast transformation, and MIF production after stimulation with five common antigens, DNA, and two nonspecific mitogens (PHA, PWM). The 6 active SLE patients were anergic and had a markedly depressed response in vitro to the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(32 citation statements)
references
References 42 publications
(33 reference statements)
2
30
0
Order By: Relevance
“…Greatly reduced numbers of T inducerhelper cells in SLE would explain, at least in part, the broad defects in cell-mediated immunity characteristic of this disorder (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Greatly reduced numbers of T inducerhelper cells in SLE would explain, at least in part, the broad defects in cell-mediated immunity characteristic of this disorder (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Our study population was a clinically stable population which was chosen to eliminate, as much as possible, the known influences of changes of disease activity and medication on immunologic function (35,36). There were no apparent differences in these factors between the normoresponsive and hyporesponsive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a substantially increased prevalence of certain of these serologic abnormalities in relatives of SLE patients, a finding suggesting that genetic factors are important in their production (5). Impaired cell-mediated immunity in SLE (6) has been related either to intrinsic cellular deficiencies (7) or to inhibiting serum factors, particularly antilymphocyte antibodies (8), or to both (9-1 1). It also has been postulated that a deficiency of "suppressor" T cells may result in heightened humoral responses (1 2).…”
Section: Genetic Immune and Viral Factors Have Been Implicated In Tmentioning
confidence: 99%